Chlorella across latitudes: investigating biochemical composition and antioxidant activities for biotechnological applications - Teoh, Ming Li; Wong, Chloe Zi En; Singaram, Nallammai; Chan, Sook Wah; Teoh, Wendy Ming Yen; Beardall, John (Editorial Office of Advances in Polar Science, 2023)
With the present day rise of interest in acquiring sustainability in the pharmaceutical industry, there has been an emphasis on finding natural resources to replace the use of synthetic compounds used in products. Microalgae have garnered significant attention owing to their natural and sustainable capability to produce a diverse array of bioactive compounds. Therefore, this study aims to evaluate the biochemical composition and antioxidant properties of Chlorella strains from a tropical region (Chlorella UMACC 051 and Chlorella UMACC 038) and a polar region (Chlorella UMACC 250 and Chlorella UMACC 234). The cultures were grown for 10 d. At the end of the experiment, the specific growth rate, chlorophyll-a content, carotenoid content, biomass, and biochemical composition such as carbohydrate, protein and lipid content were determined. In addition, the phytochemical properties were determined using a total phenolic assay while the antioxidant activities were determined using 2,2-diphenyl-1-picrylhydrazyl (DPPH). Of all Chlorella strains tested, the tropical Chlorella UMACC 051 showed the fastest growth rate and biomass while the polar Chlorella UMACC 234 contained the highest pigment content and tropical Chlorella UMACC 038 has the highest total phenolic content. The biochemical composition analysis showed all strains have a high lipid content ranging from 45.36% to 60.30% dry weight. All Chlorella strains exhibited a small amount of antioxidant activity (15.42% to 30.15%) and total phenolic content ranging from 1.91 ± 0.04 to 4.43 ± 0.10 mg GAE·g–1 dry weight. The results indicated that polar Chlorella UMACC 234 has the most potential in containing significant amounts of bioactive compounds.